PERAN WORKFORCE AGILITY TERHADAP ADAPATIVE PERFORMANCE PADA ORGANISASI SEKTOR PUBLIK BIDANG KETENAGAKERJAAN - Muhammad Eko Abrian Kusuma; Bambang Wardoyo; Nita Nurliawaty; Doni Mardiyanto; Mocamad Sarif Hasyim (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to determine the role of workforce agility on adaptive performance in public sector organizations in the employment sector. The research method used is quantitative with data collection techniques through surveys. The population in this study were all employees who work in units within the Ministry of Manpower of the Republic of Indonesia with a purposive sampling technique of 93 respondents. Data analysis in this study used IBM SPSS 25 software. Based on the results of the study, the regression results between the two variables were obtained at Y = 22,940 + 1,861X and the results of the hypothesis testing analysis through the determination test showed that the workforce agility variable had an influence of 43.7% on adaptive performance. Then from the results of the calculated t value of (8,043) > from the t table (1,990) which means Ho is rejected and Ha is accepted. The conclusion of this study is that there is a positive relationship between workforce agility and adaptive performance